A Clinical Case of Stomach Perforation Concealed by a Foreign Body - M. R. Garaev; M. Yu. Vorotnikov; Z. R. Garayeva; M. A. Nartaylakov (Креативная хирургия и онкология, 2020)
Introduction. Stomach perforations caused by ingested foreign bodies are extremely rare injuries in adults, accounting for less than 1% of all gastrointestinal perforations. The clinical picture is diverse and often presents a diagnostic problem. There are few publications reporting such cases in literature.Materials and methods. Using the example of a clinical case, this paper describes the clinical picture, diagnostic role of X-ray instruments and surgical tactics of diagnosing and treating a stomach perforation concealed by a foreign object, which occurred one week prior to admission. The patient V., 52 yo, was admitted to hospital on an emergency basis in the condition of moderate severity, complaining of abdominal pain for two days. The onset of the disease had no apparent reason. Similar pains had bothered the patient a week earlier the incident but were relieved without treatment.Results and discussion. On the basis of clinical and laboratory-instrumental data, acute pancreatitis was pre-diagnosed. Conservative drug therapy with positive dynamics was started. Two days later, computed tomography of the abdominal organs with intravenous bolus contrast was performed. According to the CT data, a foreign body in the abdominal cavity was identified, which rested on the liver at the level of the gallbladder, perforating the wall of the pyloric department of the stomach. Localized inflammatory effusion in the abdominal fat was observed. The patient was operated and discharged in satisfactory condition.Conclusion. Stomach perforations caused by small-sized foreign bodies are characterized by non-specific clinical manifestations. The use of radiation diagnostic methods facilitates the timely diagnosis and therapy choice in patients with stomach perforations caused by small-sized foreign bodies.